2016
DOI: 10.3389/fnins.2016.00348
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Focused Ultrasound Stimulation Can Modulate Phase-Amplitude Coupling between Neuronal Oscillations in the Rat Hippocampus

Abstract: Noninvasive focused ultrasound stimulation (FUS) can be used to modulate neural activity with high spatial resolution. Phase-amplitude coupling (PAC) between neuronal oscillations is tightly associated with cognitive processes, including learning, attention, and memory. In this study, we investigated the effect of FUS on PAC between neuronal oscillations and established the relationship between the PAC index and ultrasonic intensity. The rat hippocampus was stimulated using focused ultrasound at different spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Paramagnetic proteins, primarily ferritin, fused to a channel receptor function as an endogenous iron nanoparticle and enable the use of a magnetic field to modulate channel activity temporally 94,95. Low-intensity focused ultrasound has been recently used to non-invasively alter neuronal activity with high spatial resolution 96. Dysregulation of specific molecular targets has been identified in the entorhinal–hippocampal circuit 93,97,98.…”
Section: Optogenetics Sheds Light On the Hippocampal–pfc Circuitmentioning
confidence: 99%
“…Paramagnetic proteins, primarily ferritin, fused to a channel receptor function as an endogenous iron nanoparticle and enable the use of a magnetic field to modulate channel activity temporally 94,95. Low-intensity focused ultrasound has been recently used to non-invasively alter neuronal activity with high spatial resolution 96. Dysregulation of specific molecular targets has been identified in the entorhinal–hippocampal circuit 93,97,98.…”
Section: Optogenetics Sheds Light On the Hippocampal–pfc Circuitmentioning
confidence: 99%
“…Compared with more traditional neuromodulation methods such as deep brain stimulation or vagal nerve stimulation, TPU does not require the implantation of electrodes that could damage the nervous tissue or lead to infection. In many studies, TPU has been shown to induce changes in the animals' activities and neural response [82][83][84][85][86][87][88][89][90][91]. Moreover, TPU has also been experimentally observed to affect the neural activity of human beings [92][93][94] by suppression or inhibition dependent on the parameters of the acoustic energy applied to neural tissue.…”
Section: Discussionmentioning
confidence: 99%
“…As a mechanical pressure wave, pulsed ultrasound can be transmitted through the skull and facilitate or inhibit neural activities [ 8 , 9 ]. By observing the cerebral blood flow [ 10 ], LFPs or EEG signals from brain [ 11 , 12 ] or electromyography (EMG) signals from the muscle [ 13 15 ], etc., the effect of pTUS have been widely investigated. For instance, Legon W et al modulated the activity of primary somatosensory cortex and spectral content of sensory-evoked brain oscillations in humans [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Li [ 10 ] and Guo [ 17 ] used low-intensity pTUS to modulate the brain of stroke rats and found pTUS is neuroprotective for ischemic brain injury. Previously, we [ 11 ] found that the focused ultrasound stimulation could modulate the phase-amplitude coupling between neuronal oscillations in the rat hippocampus. Moreover, pTUS can stimulate the motor cortex to induce muscle contraction and EMG signals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%